2004
DOI: 10.1038/sj.eye.6701700
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of peripheral anterior chamber depth assessment in glaucoma screening

Abstract: Purpose This study was conducted to determine the usefulness of peripheral anterior chamber depth assessment in angle-closure glaucoma (ACG) screening in Japanese subjects. Subjects and methods The subjects were 14 779 adults 40 years old or older. Eyes having peripheral anterior chamber depth that is 1/4 the peripheral corneal thickness (van Herick's classification: grade 2) and less than 1/4 the peripheral corneal thickness (van Herick's classification: grade 1) were extracted as narrow angle eyes, and those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Previous studies have evaluated various screening methods for angle closure that assess the central and peripheral an-terior chamber depth (ACD). [6][7][8][9] Scanning peripheral ACD analyzer (SPAC) (model SM-70; Takagi Seiko Co, Nagano, Japan) 10 and anterior segment optical coherence tomography (AS-OCT) [11][12][13][14] are new noncontact devices that enable evaluation of the peripheral ACD and anterior chamber angle (ACA), respectively. The SPAC grading correlates well with limbal ACD assessed using the modified van Herick system.…”
mentioning
confidence: 99%
“…Previous studies have evaluated various screening methods for angle closure that assess the central and peripheral an-terior chamber depth (ACD). [6][7][8][9] Scanning peripheral ACD analyzer (SPAC) (model SM-70; Takagi Seiko Co, Nagano, Japan) 10 and anterior segment optical coherence tomography (AS-OCT) [11][12][13][14] are new noncontact devices that enable evaluation of the peripheral ACD and anterior chamber angle (ACA), respectively. The SPAC grading correlates well with limbal ACD assessed using the modified van Herick system.…”
mentioning
confidence: 99%
“…We also need to improve the algorithm of SPAC to improve the sensitivity and specificity. Compared with previous studies that employed an ultrasound system, an optical apparatus, and the van Herick technique, 7,8,10,13,14,20,22 SPAC shows similar or better performance in detecting eyes at risk of ACG, although a simple comparison of the results cannot be made (Table 3). Further, almost all of the previous studies were conducted under the guidance of an ophthalmologist, and there are few reports of angle closure screening conducted as part of a public health examination that does not involve an ophthalmologist.…”
Section: Discussionmentioning
confidence: 51%
“…As there is a strong association between shallow anterior chamber and PACG, the measurement of anterior chamber depth (ACD) may be useful in screening eyes for PACG. [7][8][9][10][11][12] Eyes with ACG or narrow angle eyes at risk of ACG have been screened with different methods. 7,11,[13][14][15] However, those methods present several disadvantages including low accuracy, invasiveness, expensiveness, low reproducibility, handling difficulty, and time-consuming analysis, which interfere with their widespread use in routine clinical practice or glaucoma screening.…”
mentioning
confidence: 99%
“…It is equipped with an autofocusing system for anterior chamber depth, an automeasuring system for determining central corneal thickness and corneal radius of curvature, an autodiagnosing program for differentiating eyes with narrow angles and an autoclassifying program for categorizing eyes in subgroups according to anterior chamber depth values 26 . The SPAC has been shown to measure anterior chamber depth with good accuracy and reproducibility and therefore has been suggested as a useful tool for glaucoma screening 27,28 . Whereas one study found that SPAC measurements of anterior chamber configuration correlated well with conventional methods such as Shaffer grading, van Herick grading and UBM, 29 other studies have found that its lower specificity in the detection of narrow angles limits its use in screening 30,31 …”
Section: Other Anterior Segment Imaging Devicesmentioning
confidence: 99%